Factors Affecting Capital Structure in Plastics Manufacturing Enterprises in Northern Vietnam - Nga, Nguyen Thi Viet; Binh, Nguyen Van (Business and Economic Research, 2023)
<span style="color: #000000; font-family: Verdana, Arial, Helvetica, sans-serif; font-size: 10px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: start; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial; display: inline !important; float: none;">There are various perspectives on capital in economics. Some economists argue that capital encompasses all economic factors arranged to produce goods and services, including financial assets, as well as knowledge about the economic and technical aspects of the business. Through practical research conducted in the plastics manufacturing industry in Northern Vietnam, the author identifies the factors influencing the capital structure, including subjective and objective factors. Based on these findings, appropriate solutions are proposed to improve the capital structure within enterprises.